Studies of a Fibrinolytic Enzyme from the Larvae of Lonomia achelous (Cramer) Using Chromogenic Peptide Substrates - Arocha-Piñango, C L; Pepper, D S (Thrombosis and Haemostasis, 1981)
A fibrinolytic agent purified from the haemolymph, hair secretion and whole body extract of Lonomia achelous (Cramer)cleaves various chromogenic peptide substrates. The best substrate were found to be pyro-Glu-Gly-Arg-pNA (S-2444) followed by D-Pro-Phe-Arg-pNA (S-2302) and Bz-Ile-Glu-(or) Gly-Arg-pNA (S-2222) designed for urokinase, plasma kallikrein and factor Xa, respectively. Using substrate S-2251 we also found a plasminogen activator.
Keywords: Chromogenic substrates; Caterpillar extract; Fibrinolytic enzymes